Abigail Adams : first lady of the American Revolution - Lakin, Patricia, 1944- (Ready-to-read stories of famous Americans, 2006)
Presents a short biography of Abigail Adams, wife of the second President of the United States; and chronicles her childhood in Massachusetts, education, marriage, and the role she played in helping to shape the early history of America.